The Relationship Between Knowledge, Attitudes, and Pocket Money and Food Safety Behavior Among Students at Mulyasari Patokbeusi Public Elementary School in 2025 - Ajay Rana; Sudiono; Saleh Budi Santoso (INDOGENIUS, 2026)
Background & Objective: Food is a basic necessity that must meet safety standards to be safe for consumption and not pose a health risk. This study aims to analyze the factors associated with food safety behavior among students at SDN Mulyasari Patokbeusi in 2025. Method: A quantitative cross-sectional design was used, involving 97 respondents selected via purposive random sampling. Data were collected using a questionnaire and analyzed using the Chi-square test. Result: The results indicate that attitude has a significant association with food safety behavior (p = 0.014; OR = 4.154; 95% CI: 1.284–13.441). Knowledge did not show a significant relationship (p = 0.613; OR = 1.292; 95% CI: 0.476–3.504), nor did pocket money (p = 1.000; OR = 1.158; 95% CI: 0.285–4.708). Conclusion: These findings indicate that students’ attitudes play a greater role in determining food safety behavior than knowledge and the amount of pocket money they have.